2010
DOI: 10.4314/ajfand.v9i7.47678
|View full text |Cite
|
Sign up to set email alerts
|

Role of livestock projects in empowering women smallholder farmers for sustainable food security in rural Kenya

Abstract: Women are a major human resource and assure adequate nutrition, health and cognitive development of their households and children in their formative years. However, women are over-represented among the poor, suffer heavy workloads and have little control over resources for family care. Poverty and food insecurity are enhanced by lack of access to, and control over assets, and lack of access to institutions that provide opportunities and buffer from shocks and crises. The need to improve household food security… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…"Intermediate" was used to describe the dairy production and livelihood asset and outcome measurements for one-to three-year members. Other studies found higher milk production, average per-capita milk consumption, and income from milk sales among farmers involved in dairying for at least three years (Lwelamira et al, 2010;Walingo, 2009). We assert that this early period is needed to enhance women's capacity and confidence to use their limited resources for enhanced milk production.…”
Section: Household Food Securitymentioning
confidence: 62%
See 1 more Smart Citation
“…"Intermediate" was used to describe the dairy production and livelihood asset and outcome measurements for one-to three-year members. Other studies found higher milk production, average per-capita milk consumption, and income from milk sales among farmers involved in dairying for at least three years (Lwelamira et al, 2010;Walingo, 2009). We assert that this early period is needed to enhance women's capacity and confidence to use their limited resources for enhanced milk production.…”
Section: Household Food Securitymentioning
confidence: 62%
“…Herd size for nonmembers reflected the median herd size of 1.3 animals reported for smallholders in the Kenyan highlands (Bebe, 2003). Increased milk production and incomes of smallholder farmers resulting from the use of cross-bred cows and better livestock management through farmer training, has been reported after two to four years in Ethiopia (Ahmed et al, 2000) and after three years in Kenya (Walingo, 2009). Sustained higher milk production with longer WDL membership may be attributed to the ability of WDL to market and pay for milk and to women retaining control of dairy income.…”
Section: Farm Production and Financial Capitalmentioning
confidence: 99%
“…Differences in rates of decline between intervention and control groups were not reported. Neither the HFP programme in Cambodia 46 nor a dairy project in Kenya 61 reported significant changes in women's weight or BMI.…”
Section: Resultsmentioning
confidence: 95%
“…In total, 17 articles reported on health and nutrition outcomes of women, usually the mother of an index child 30,33,34,36,42,43,45–47,49,55–59,61,62 All reported diet and/or nutrient intakes; three reported anaemia outcomes; three reported anthropometry and one reported morbidity data. No studies reported on the VA status of women.…”
Section: Resultsmentioning
confidence: 99%
“…Potato (5) de;Hagenimana et al (1999);Hagenimana et al (2001); Jones and de Brauw (2015);Low et al et al (2002b)/(Faber et al 2002a);(Laurie and Faber 2008);(Smitasiri et al 1999);(Vijayaraghavan et al 1997) Diversification (17) Home Production: Diversified (11) Bezner Kerr et al (2011); Bushamuka et al (2005); English et al (1997) / English and Badcock (1998); Greiner and Mitra (1995); (Kaufer et al 2010); Langworthy and Caldwell (2009); Schmidt and Vorster 1995; Marsh (1997) / Talukder et al (2000); Taher et al . (1999) / Kassa et al (2003); Hoorweg et al (2000); Miller et al (2014); Rawlins et al(2014);Walingo (2009) or add to food production activities, necessitate shifting or new food consumption behaviors, and fit into a complex political, economic and environmental context. As we develop and strengthen agricultural interventions that improve nutrition, our typologies provide a tool to differentiate among this set of interventions.…”
mentioning
confidence: 99%